1996
DOI: 10.1053/jhep.1996.v24.pm0008707268
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin induced contractility of stellate cells from normal and cirrhotic rat liver: implications for regulation of portal pressure and resistance

Abstract: by two major endothelin receptors, endothelin A (ET A ) and Hepatic stellate cells are similar to tissue pericytes endothelin B (ET B ). 2-3 ET A receptors are abundant on vascuand have been shown to be contractile. In this study, we lar smooth muscle cells, have a high affinity for endothelinexamined the effects of known mediators of stellate cell 1, produce sustained contraction of vascular smooth muscle contraction on portal pressure in rat livers after carbon cells, and mediate vasoconstriction. 3 In contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
134
0
8

Year Published

1998
1998
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(147 citation statements)
references
References 14 publications
5
134
0
8
Order By: Relevance
“…However, unlike ET-1, upregulation of ET A and ET B receptor gene expression was closely related with HVPG. These findings are in keeping with previous investigations demonstrating that nonselective endothelin receptor antagonists [27, 29], but not selective antagonists for the ET A receptor [13], moderately albeit significantly reduce portal pressure in cirrhotic rats.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, unlike ET-1, upregulation of ET A and ET B receptor gene expression was closely related with HVPG. These findings are in keeping with previous investigations demonstrating that nonselective endothelin receptor antagonists [27, 29], but not selective antagonists for the ET A receptor [13], moderately albeit significantly reduce portal pressure in cirrhotic rats.…”
Section: Discussionsupporting
confidence: 92%
“…These cell types express both ET A and ET B receptor, but until very recently it was thought that cell constriction induced by ET-1 was solely mediated by the ET A receptor [3]. However, the availability of selective ET B receptor agonists has evidenced that ET B receptor can also mediate contraction in the liver [27] and isolated stellate cells of rats [28]. The ET B -mediated vasoconstrictor response has also been observed in human nonhepatic vascular beds [7].…”
Section: Discussionmentioning
confidence: 99%
“…Elevated endothelin-1 plasma and hepatic tissue concentrations correlate with the severity of cirrhosis and the hepatic venous pressure gradient (HVPG) [6,8]. Several experimental studies have shown that oral administration of bosentan, a dual ET A and ET B receptor antagonist, significantly reduced the degree of portal hypertension in cirrhotic rats [10][11][12]. The effects of this class of drugs have, however, never been evaluated on the splanchnic circulation in patients with cirrhosis and portal hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…In normal livers, ET-1 is reported to contract not only portal venules but also hepatic sinusoids [56,57]. The contractility of hepatic sinusoids by ET-1 is ascribed to that of hepatic stellate cells [40,43]. However, no investigators measured the sinusoidal resistance of the liver administered of ET-1 or determined which hepatic vascular segments of the portal veins, the sinusoids, and the hepatic veins most extensively contract in response to ET-1.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, in cirrhotic patients and animals, abnormal splanchnic and systemic vasodilation [24,44] and the hyporeactivity of these vessels to vasoactive substances [13,55] are well known, which are presumably caused by increased NO production. However, the hepatic vascular responsiveness to vasoconstrictors such as ET-1 is varied in animals with liver cirrhosis; it is increased [10,40] or decreased [21,22]. Furthermore, it is possible that the vasoreactivity may be variable depending on the hepatic vascular segments.…”
Section: Introductionmentioning
confidence: 99%